Mice Oocytes Respond after Vitrification Followed by Artifical Activation Using a Various Concentration of Strontium Chloride and Cytochalasin B - Ridlo, Muhammad Rosyid; Widyastuti, Rini; Lubis, Alkaustariyah; Fahrudin, Mokhamad; Boediono, Arief (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Oocyte vitrification is the important part of gamete preservation for further purpose. The objective of this study was to evaluate the response or development of vitrified-mice oocyte following activation using various concentrations of Strontium Chloride (Sr Cl2). Oocytes were collected from superovulation-induced female mice. Oocytes vitrification was then performed using a gradual equilibration of 2 M Ethylene Glycol in 0.25 M sucrose and 7 M Ethylene Glycol on 0.5 sucrose. Subsequently, the vitrified oocytes were thawed and activated using various Strontium Chloride concentration in each group. Control 1 is unvitrified oocyte and without Sr Cl2. Control 2 is unvitrified oocyte then activated by 20 mM Sr Cl2. Zero (0) mM  Sr Cl2 is vitrified oocyte without Sr Cl2. Group Ten (10) mM is vitrified oocyte then activated by 10 mM Sr Cl2. Group Twenty (20) mM is vitrified oocyte then activated by 20 mM Sr Cl2. The viability of vitrified-thawed oocytes was observed based on ooplasm integrity. Whereas the oocytes respond to artificial activation was observed based on pronucleus formation after 10 hours of activation. The result showed that 39% of oocyte degenerated following vitrification. The respond of vitrified-thawed oocytes following artificial activation using Strontium Chloride was significantly lower compared to fresh oocytes (p<0,05). Interestingly the highest percentage of activated oocytes (36.36%) was present in a group achieved 20 mM Strontium Chloride. As conclusion is Strontium Chloride 20mM has a best result (36,36%) to activate vitrified oocyte than 0 mM and 10 mM of Strontium Chloride.